2018
DOI: 10.1111/1467-9477.12129
|View full text |Cite
|
Sign up to set email alerts
|

Participation in Indigenous Democracy: Voter Turnout in Sámi Parliamentary Elections in Norway and Sweden

Abstract: This article compares and analyzes voter turnout in the 2013 elections to the Sámi parliaments in Norway and Sweden, using data from voter surveys. Is voting in these elections motivated by the same factors that explain turnout in national parliamentary elections? First, the study showed that a common election day for national and Sámi elections is an important reason for the higher turnout in Norway. Second, involvement in Sámi society was the most important factor for explaining turnout in both countries. Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Partly due to this, turnout is lower in Sweden. 30 In Swedish S amediggi elections, the entire country constitutes a single constituency (with 31 seats), while Norway's S amediggi (with 39 seats) is elected from seven multi-member constituencies. Moreover, voting for individual candidates has no effect in Norway, whereas personal votes are important for electing candidates in Sweden.…”
Section: Institutional Context: the Two S Amediggismentioning
confidence: 99%
See 1 more Smart Citation
“…Partly due to this, turnout is lower in Sweden. 30 In Swedish S amediggi elections, the entire country constitutes a single constituency (with 31 seats), while Norway's S amediggi (with 39 seats) is elected from seven multi-member constituencies. Moreover, voting for individual candidates has no effect in Norway, whereas personal votes are important for electing candidates in Sweden.…”
Section: Institutional Context: the Two S Amediggismentioning
confidence: 99%
“…Using data from the 2009 S ami Election Study in Norway and the 2013 S ami Election Studies in both countries, earlier studies suggested that the cleavages discussed above are also reflected in voter attitudes. 51 In this article, we use data from the 2017 S ami Election Studies that were carried out in Norway and Sweden. Both election studies are based on random samples of registered voters drawn from the electoral roll.…”
Section: Survey Datamentioning
confidence: 99%
“…Elections are a concept of procedural democracy (Júnior & Salgado, 2021;Saffon & González-Bertomeu, 2017;Saffon & Urbinati, 2013;Simon, 2018) , elections are also the strongest force for the people to participate in modern representative democracy (Bergh et al, 2018;Freitag & Stadelmann-Steffen, 2010;Henn & Foard, 2014) . In Indonesia, the electoral system that is run is useful for filling positions of people's representatives such as President and Vice President, DPR members, DPD members, Provincial DPRD members, Regency DPRD members, and City DPRD members (Gallagher, 2011;Hillman, 2018;Junaidi, 2020 ;Suwitri et al, 2019) .…”
Section: Introductionmentioning
confidence: 99%